Preparatanvändning och ogräsförekomst på gårdar med olika jordbearbetningsstrategier - Gunnarsson, Björn-Christian (SLU/Dept. of Soil and Environment, 2011)
Reduced tillage has increased in Sweden during several years, primarily to decrease costs and increase efficiency in crop production. Despite this, mouldboard ploughing is still the most common primary tillage method on most farms. The aim with this thesis was to compare the use of pesticides and the occurrence of weeds on ten farms in Skåne and ten farms in Mälardalen that use different soil tillage systems. The object of the study was also to clarify why the farms had chosen their specific soil tillage system and the consequences it has had on weed occurrence and use of pesticides. The result showed a slightly higher use of pesticides on the farms that use reduced tillage. According to the farmers interviewed in Skåne, occurrence of weed was considered higher in reduced tillage, while the result in Mälardalen was the opposite. More weed species were considered hard to control in Skåne as well as in Mälardalen on the farms that used reduced tillage.